Rejuvenation Of State Ships To Drive Decarbonization Of The Shipping Sector - Danawiryya Silaksanti; Tri Cahyadi; Winarno (International Journal of Marine Engineering Innovation and Research, 2025)
In line with the 2023 IMO GHG Strategy, adopted at the 80th Marine Environment Protection Committee (MEPC 80) on the Reduction of GHG Emissions from Ships, Indonesia has been implementing climate action that aligns with its national policy to combat climate change. The Government of Indonesia has been making efforts to rejuvenate state ships, specifically navigation and patrol ships, by building new ships and scrapping old ones. This study assessed the potential for reducing greenhouse gas emissions from state ship construction activities using modern technology. It analyzed operational data for each ship's specifications, such as fuel type, power, and gross tonnage. The study showed that the GHG emission reduction from this activity in 2023 is 128.564,39 tons of CO2, resulting from the 22 new ships built between 2019 and 2023. The construction of these new ships demonstrates the government’s commitment to reducing emissions from the operation of state ships by eliminating older ships. It is hoped that if commercial ships are also scrapped and replaced with new ones built using more modern technology that saves fuel, this will enhance efforts to reduce emissions from the shipping sector and encourage maritime decarbonization.